PENGARUH KEPEMIMPINAN TERHADAP BUDAYA ORGANISASI INOVASI DAN KINERJA KARYAWAN (STUDI KASUS PADA KANWIL PT. PEGADAIAN (PERSERO) DENPASAR) - salain, pradiva putra (E-Jurnal Manajemen, 2013)
The purpose of this study was to determine the effect of transformational and transactional leadership on organizational innovation culture and employee performance. The number of samples in this study were 131 employees sampled. Hypothesis testing using structural model analysis techniques (SEM analysis), with the tools of SPSS (statistical package for social science) and AMOS (analysis of moment structure) The results showed that: (1) transformational leadership has a positive effect on the performance of employees in the Office (2) transactional leadership has a positive effect on employee performance at the Office of (3) the positive effect of transformational leadership on organizational culture of innovation at Office (4) the positive effect of transactional leadership on organizational culture in the Office, and (5) organizational culture of innovation has a positive effect on employee performance in the Office Suggested to the next researcher to examine the variables that influence organizational culture and employee performance and innovation for the company is advised further improve the quality of leadership styles in order to maintain the company's organizational culture Normal 0 false false false EN-US X-NONE X-NONE
Keywords: transformational leadership, transactional leadership, organizational culture of innovation and employee performance